2020
DOI: 10.3892/mmr.2020.11769
|View full text |Cite|
|
Sign up to set email alerts
|

miR‑182‑5p contributes to radioresistance in nasopharyngeal carcinoma by regulating BNIP3 expression

Abstract: Radioresistance is the primary roadblock limiting the success of treatment of nasopharyngeal carcinoma (NPC). microRNA (miRNA/miR)-182-5p has been reported to affect the sensitivity of cancer cells to irradiation; however, the role of miR-182-5p in NPC has not been assessed. The aim of the present study was to investigate the contribution of miR-182-5p to the radioresistance of NPC cells. The key mRNA and miRNA involved in NPC radioresistance were identified using bioinformatics analysis. The two cell lines us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…The neuroprotective effect of miR-182 in mice following SCI was a consequence of the suppression of apoptosis in neurons [48]. It was also shown that the inhibition of miR-182-5p increased the sensitivity to irradiation in nasopharyngeal carcinoma cells, suggesting that miR-182-5p contributes to cellular radioresistance [49]. Accordingly, miR-182 was upregulated in lung cancer, and its inhibition sensitized cancer cells to ionizing radiation by suppressing cell proliferation and increasing cell apoptosis after irradiation, suggesting that miR-182 might account for radioresistance in lung cancer [50].…”
Section: Discussionmentioning
confidence: 98%
“…The neuroprotective effect of miR-182 in mice following SCI was a consequence of the suppression of apoptosis in neurons [48]. It was also shown that the inhibition of miR-182-5p increased the sensitivity to irradiation in nasopharyngeal carcinoma cells, suggesting that miR-182-5p contributes to cellular radioresistance [49]. Accordingly, miR-182 was upregulated in lung cancer, and its inhibition sensitized cancer cells to ionizing radiation by suppressing cell proliferation and increasing cell apoptosis after irradiation, suggesting that miR-182 might account for radioresistance in lung cancer [50].…”
Section: Discussionmentioning
confidence: 98%
“…Also, silent mating-type information regulator 2 homolog 1 ( SIRT1 ) is significantly down-regulated in DF patients, and the C allele of rs12778366 polymorphism of the SIRT1 gene may be a protective factor for DF ( 9 ). Moreover, the overexpression of taurine-upregulated genes 1 ( TUG1 ) can restore endothelial progenitor cells (EPC) function after HG treatment by regulating the miR-29c-3p /PDGF-BB/Wnt signaling pathway ( 10 ). The upregulation of active-matrix metalloproteinase (MMP-9) results in diabetic wound healing difficulties in mice, and the inhibitor of MMP-9 is expected to be an effective treatment ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, it was observed that some genes were differentially expressed in DFU and control groups, which played different roles in the occurrence and development of diseases through different mechanisms of action (8)(9)(10)(11)(12)(13). For example, rs1024611 polymorphism of the monocyte chemoattractant protein-1 (MCP-1) gene is significantly correlated with MCP-1 expression and individual susceptibility to DFU (8).…”
Section: Discussionmentioning
confidence: 99%
“…To date, several studies have demonstrated that miRNAs regulating ferroptosis are associated with the proliferation, invasion, migration and apoptosis of NPC cells, particularly in terms of radiosensitivity regulation ( Table I ). For instance, miR-214 and miR-182-5p were indicated to contribute to radioresistance in NPC by regulating LTF and BNIP3 expression ( 103 , 104 ). However, miR-124 and miR-9 may promote radiosensitivity of NPC via targeting programmed cell death protein 6 (PDCD6) and suppressing the expression of junctional adhesion molecule A (JAMA) ( 105 – 107 ).…”
Section: Mirnas Regulating Ferroptosismentioning
confidence: 99%